The application of multicriteria decision analysis in an ISO 9001 implementation problem - Cabecinhas, Mónica Paula Ferreira (2018)
Nowadays, organizations are challenged with several problems which envolve financial and non-financial impacts. Several tools and methodologies had been created to help them in the process of decision making. These methodologies have in consideration the important aspects for the companies and the possible results obtained for each criteria under analysis. In the presented study, we used a decision making methodology based on value functions, to help make decisions in a context of an hyphotetical problem related with the impacts of the ISO 9001 implementation. This is one of the most used methods for multi-criteria decision analysis. This study shows the utility of this method to solve problems with both types of criteria, financial and non-financial. Besides, it allowed to identify limitations of the application of this kind of methods such as the dependency of the opinion of the decision maker, that could result in different outcomes, according to his preferences. To mitigate this problem, a combination of decision making methodologies could help to achieve better results.